Penentuan Interval Waktu Penggantian dan Perbaikan Komponen Kritis Mesin Bubut Type SS-850 di PT. Hamdan Jaya Makmur Dengan Metode Age Replacement - Rachman, Taufiqur; Watunglawar, Darmiolla Natasia; Amperajaya, M. Derajat; Adnan, Septian Rahmat; Sriwana, Iphov Kumala (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2022)
PT. Hamdan Jaya Makmur is a company that runs in the field of Machining, Engineering, Fabrication, Stamping, and Trading Company, which produces products for small, medium and modern industries. Less than optimal maintenance system with corrective maintenance causes PT. Hamdan Jaya Makmur often experiences machine failure. Based on historical data, it can be seen that the lathe machine type SS-850 experienced very high downtime. Therefore, it is necessary to plan optimal and preventive maintenance of the machine in order to produce according to the target and increase the reliability of the machine. The purpose of this research is to determine the time interval and cost of preventive replacement on components of the lathe machine type SS-850 at PT. Hamdan Jaya Makmur. The method used in this research is the Age Replacement method, namely by determining critical components, determining the distribution pattern of damage, determining distribution parameters, and calculating MTTF and MTTR, where the results obtained are preventive replacement time intervals, and calculating preventive replacement costs. The results obtained from this research are that there are four critical components on the lathe machine type SS-850, namely electric components with a preventive replacement time interval of 11 days and a preventive replacement cost of Rp.3,080,679,253, bearing components have a preventive replacement time interval of 14 days and a preventive replacement cost of Rp.4,931,989,307, the gearbox component has a preventive replacement time interval of 33 days and a preventive replacement cost of Rp.11,621,532,829, and bolt and nut components have a preventive replacement time interval of 11 days and a preventive replacement cost of Rp.1,615,296,412.